Disruption of the MreB Elongasome Is Overcome by Mutations in the Tricarboxylic Acid Cycle - Barton, Brody; Grinnell, Addison; Morgenstein, Randy M. (Frontiers in Microbiology, 2021)
The bacterial actin homolog, MreB, is highly conserved among rod-shaped bacteria and essential for growth under normal growth conditions. MreB directs the localization of cell wall synthesis and loss of MreB results in round cells and death. Using the MreB depolymerizing drug, A22, we show that changes to central metabolism through deletion of malate dehydrogenase from the tricarboxylic acid (TCA) cycle results in cells with an increased tolerance to A22. We hypothesize that deletion of malate dehydrogenase leads to the upregulation of gluconeogenesis resulting in an increase in cell wall precursors. Consistent with this idea, metabolite analysis revealed that malate dehydrogenase (mdh) deletion cells possess elevated levels of several glycolysis/gluconeogenesis compounds and the cell wall precursor, uridine diphosphate N-acetylglucosamine (UDP-NAG). In agreement with these results, the increased A22 resistance phenotype can be recapitulated through the addition of glucose to the media. Finally, we show that this increase in antibiotic tolerance is not specific to A22 but also applies to the cell wall-targeting antibiotic, mecillinam.